Accurate Bayesian phylogenetic point estimation using a tree distribution parameterized by clade probabilities. - Lars Berling; Jonathan Klawitter; Remco Bouckaert; Dong Xie; Alex Gavryushkin; Alexei J Drummond (PLoS Computational Biology)
Bayesian phylogenetic analysis with MCMC algorithms generates an estimate of the posterior distribution of phylogenetic trees in the form of a sample of phylogenetic trees and related parameters. The high dimensionality and non-Euclidean nature of tree space complicates summarizing the central tendency and variance of the posterior distribution in tree space. Here we introduce a new tractable tree distribution and associated point estimator that can be constructed from a posterior sample of trees. Through simulation studies we show that this point estimator performs at least as well and often better than standard methods of producing Bayesian posterior summary trees. We also show that the method of summary that performs best depends on the sample size and dimensionality of the problem in non-trivial ways.